Genetic Diversity of Human Leishmania spp. Isolated from an Endemic Area in the Middle of Iraq - Amany Mohamed Al-Kasy (Journal of Global Pharma Technology, 2016)
This study aimed to the possible characterization of cutaneous leishmaniasis species isolated from cutaneous tissue imprints from patients in an endemic area in the middle of Iraq. Samples were taken by skin scraping and dermal tissue aspiration. Direct examination and polymerase chain reaction, two types of primers used (CL for L. major, Lin R for L. tropica) for detection. DNA Sequencing and phylogenetic analysis were also used for detection. In this study, 48 patients with Cutaneous leishmaniasis were enrolled, 32 (66.7 %) of them were males and 16 (33.3%) were females. Giemsa staining results showed presence of 25 amastigote forms inside and outside the macrophages, while 25 (53 %) and 23 (47 %) were positive to direct test, 26 (54.2 %) patients had multiple lesions and 22(45.8%) had single lesions in a different locations of the body. More than 68.8% of patients had dry lesions, while 27.1% had moist and 4.2 % had mixed lesions. The results showed that 8 isolates (16.7 %) were L. tropica and 4 cases were L. major (8.3 %). Most L. tropica lesions were located on the face and other parts of the body, while lesions of L. major were located on foot. In addition, new species of Leishmania were identified as L. infantum 3 (6.3 %). Four PCR products of L. major isolates were prepared and sequenced by Macrogen Company, USA. The sequence of the isolates was recorded in the gene bank and the accession numbers of L. major were LC369673, LC369674, LC369675 and LC369676. The phylogenetic tree constructed from these sequences and the polygenetic tree of the L. major. The Iraqi isolates were close to French and Russian isolates.Keywords: Cutaneous leishmaniasis, PCR, Sequencing, Phylogenetic.